Clickboat Click Boat: Boat Repair and Rental Management System - Placio, Calvin John Villaluna; Paytaren, Albert V. (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose   – The general objective of the study is to develop a web/mobile application that can be used by yacht owners, yacht charter, tourists, and boat owners. To be able to understand the main objective, the specific objectives were drawn: (1) Define problems encountered in: a. Yacht repair scheduling, b. Yacht repair management, c. tourist itinerary,d. boat scheduling;(2) Define modules of the system developed to address the problem;(3) the level of acceptance of the respondents in the developed system in terms of: a. user-friendliness, and functionality ; (4) Issues encountered during the initial deployment of the system. Method – To be able to develop the final output, the study followed the processes involved in Agile Development. It includes all the processes that are necessary to finish the study which are: (1) Plan, (2) Design, (3) Develop, (4)Test, (5) Release, and (6) Feedback. The data needed to conduct the study were analyzed and validated based from the system requirements of the project. Results – The developed system's evaluation resulted in the mean range of 4 above with the equivalent of a high acceptability rating for both user-friendliness and functionality. The developed modules are for tourists, yacht charter, yacht owners, and boat owners where they can communicate and automate some of the processes that involve notification and report generation. Conclusion – Mobile and web application is a good way to cater to marina-based services such as boat repair and rental. Different available API and libraries are very useful in the development because it speeds up the process. The ability to test different environments of the system is a must especially since technology is evolving. Recommendations – Due to the system's high acceptability rating from the users the marina business may try to pursue the usage of management systems that involves automation of the processes they needed such as user notifications and report generations. The developed system can be improved to make it more useful for the marina businesses such as boat repair and rentals. Research Implications – Marina-related businesses are not typical kinds of businesses most clients and service provider encounter difficulty in terms of using the traditional system. With the use of technology, we can improve the process and especially attract more customers because the service is one click away to be availed.